2014
DOI: 10.1371/journal.pone.0095660
|View full text |Cite
|
Sign up to set email alerts
|

Good Fences: The Importance of Setting Boundaries for Peaceful Coexistence

Abstract: We consider the conditions of peace and violence among ethnic groups, testing a theory designed to predict the locations of violence and interventions that can promote peace. Characterizing the model's success in predicting peace requires examples where peace prevails despite diversity. Switzerland is recognized as a country of peace, stability and prosperity. This is surprising because of its linguistic and religious diversity that in other parts of the world lead to conflict and violence. Here we analyze how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 77 publications
(27 reference statements)
3
15
0
Order By: Relevance
“…This interpretation clearly contradicts the original HA’s (2006b) argument. However, it is broadly consistent with Hartshorn et al’s (2013) and Rutherford et al’s (2014) analyses and, what is especially relevant, with recent empirical findings. For instance, Bernhard, Fischbacher, and Fehr (2006) found evidence of “parochialism” in a field experiment in Papua New Guinea, where participants did not transfer higher amounts of money when paired with subjects belonging to the same ethnic group in a dictator game but harshly punished out-group participants not respecting the “fair-share” norm.…”
Section: Discussionsupporting
confidence: 88%
“…This interpretation clearly contradicts the original HA’s (2006b) argument. However, it is broadly consistent with Hartshorn et al’s (2013) and Rutherford et al’s (2014) analyses and, what is especially relevant, with recent empirical findings. For instance, Bernhard, Fischbacher, and Fehr (2006) found evidence of “parochialism” in a field experiment in Papua New Guinea, where participants did not transfer higher amounts of money when paired with subjects belonging to the same ethnic group in a dictator game but harshly punished out-group participants not respecting the “fair-share” norm.…”
Section: Discussionsupporting
confidence: 88%
“…ey found that ethnic violence did not occur when the ethnic groups were either well mixed or well separated but rather occurred only when ethnic groups separated into geographic patches (this separation falls into the same universality class as the separation of oil and water), with the violence most likely to occur for geographic patches of a particular size. is analysis implies that ethnic violence can be prevented by the use of well-placed political boundaries, as in Switzerland [67]. Although not explicitly included in the analysis, specific details of a region are relevant insofar as they are either a cause or an effect (or both) of the patch size-for instance, animosity between two ethnic groups, though not explicitly considered, may be a cause as well as a consequence of geographic segregation [68].…”
Section: Understanding Complex Systemsmentioning
confidence: 99%
“…Finally, scholars have long emphasized how spatial factors, especially distance between peoples, shape network structures, identities and preferences (Lipset and Rokkan, 1967;Rokkan and Urwin, 1983;Jenkins, 1986;Rutherford et al, 2014), and this is also true in the case of Jura; indeed, it was the focus of the first systematic study of the Jurassien question (Jenkins, 1986). To measure distance, we calculated travel distance to Delémont (the capital of Jura) by car in minutes using Google maps (2014).…”
Section: Figure 3: Share Of Yes Votes In Jura Bernois 2013mentioning
confidence: 99%
“…The last approach is structuralist . Some of these accounts are based on the idea that the social networks that facilitate collective action are fundamentally constrained by geographic factors, such as distance and topography (Rokkan and Urwin, 1983; Jenkins, 1986; Lipset and Rokkan, 1990 [1967]; Rutherford et al ., 2014). For example, the greater the distance from a center to its peripheries, ‘the greater the risk that these will become the nuclei of independent center formation’ (Rokkan and Urwin, 1983: 16), hence the looser the bonds that tie the two together and the more likely secession is to occur.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation